Defy the worlds - Gray, Claudia (Gray, Claudia. Defy the stars, 2018)
"Sophisticated robot Abel must save teenaged soldier Noemi from capture on a hidden planet, while outwitting armies of deranged service robots and securing medical aid for a plague on Noemi's home world"--